To solve the equation \( \frac{1}{3}(6x - 9) = -33 \), let's go through the steps logically:
Step 1
Multiply both sides by 3 to eliminate the fraction: \[ 6x - 9 = -99 \]
Step 2
Add 9 to both sides to isolate the term with \(x\): \[ 6x = -90 \]
Step 3
Divide both sides by 6 to solve for \(x\): \[ x = -15 \]
Based on that, you can fill in the steps as follows:
- Step 1: Multiply both sides by 3.
- Step 2: Add 9 to both sides.
- Step 3: Divide by 6.
Answer to Question 2
Therefore, the answer to \( x \) is: \[ x = -15 \]